Tradução para português e validação cultural da Empowerment Assessment Rating Scale - Melo, Pedro (2020)
Introduction | To assess the level of community empowerment, Laverack proposes an instrument called the Empowerment Assessment Rating Scale (EARS), which has nine assessment domains related to community empowerment. Objectives | Translate to Portuguese and culturally validate the EARS for an ACeS community, a hospital community, a business community, and a school community. A review of the Portuguese translation was developed, a review group was set up to analyze the resulting document, by consensus a new scale called the Escala de Avaliação do Empoderamento Comunitário (EAvEC) was developed, and the retroversion was developed. Same review group conducted a new evaluation of the resulting version, comparing them with the original in English. The study was carried out at a Hospital in the Azores Archipelago, three Health Centers Organizations in the North of Portugal, an Education-oriented Company in Greater Porto and a School Communityin Mozambique, where the focus group scale was applied based on a problematic chosen for intervention. Results | EVaECretained the nine evaluation domains of the original scale and its translated version did not change after its cultural adaptation. The level of community empowerment was identified in each of the communities, analyzed in the form of a radar chart, with the clustered image of all domains. Discussion / Conclusions | EVaEC is a useful tool for community intervention and is being used to assess community empowerment in the MAIEC project of theCentre for Interdisciplinary Research in Health at Universidade Católica Portuguesa.